The Effect of Financial Ratio on Stock Price Volatility - Crisanti, Stephanie; Cahyani Nuswandari; Sunarto (Jurnal Wacana Ekonomi, 2024)
This research aims to examine the influence of financial ratios, namely TATO, EPS, ROA, and DER on company share price volatility. This information provides a signal about the company's prospects to external parties, especially investors. The population used in this research includes companies in the energy, industrial, technology and infrastructure sectors listed on the Indonesia Stock Exchange (BEI) with observation years 2020 to 2022. Sample selection used a purposive sampling technique. The total population is 215 companies with a total sample that meets the criteria of 169 companies. The analysis technique used is Multiple Linear Regression analysis with a total of 165 data processed. The results of this research show that the TATO variable has a significant positive effect on stock price volatility, while the EPS, ROA and DER variables have no effect on stock price volatility. In general, this research provides consideration of factors that influence stock price volatility for investors in investing decisions.